Comparison of the performances of two commercial membranes in hardness removal from underground water using Nanofiltration membranes - fatima, Elazhar; ELHABBANI, Redoune; Elazhar, Maryem; Hafsi, Mahmoud; Elmidaoui, AZZEDDINE (International Journal of Advanced Chemistry, 2013)
In this works, the comparison of the performances of two commercial membranes in hardness removal by nanofiltration in continuous mode was investigated from synthetic ground water of Maâmoura doped for various concentrations of TH (CaCl2, MgCl2). The experiments were carried out in the pressure range of 6–40 bars. Analyses of the samples, and permeates at different pressures, were performed and the effects of the trans-membrane pressure on the permeate flux and salt rejection were studied. Also the study presents the effect of salinity of the performances of two tested membranes (NF90 and NF270). Many configurations were tested: simple pass, double pass with one type of membranes and combination of two types of membranes. The pilot used (supplied by the French Company TIA) is an industrial nanofiltration pilot plant having two modules equipped with various spiral commercial membranes with an area of 7.6 m2.